Pendampingan Edukasi Kepramukaan dan Sejarah Kemerdekaan di SDN 08 Kaubun - Hartono, Hartono; Najwa, Putri Zarifah; Ramadhan, Muhammad Syahrul; Derby, Muhammad; Prayoga, Agry; Nurbia, Eki (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
The main objective of this activity is to improve students' understanding of national values ​​and basic Scouting skills that are important in character building. The method used in this mentoring is an interactive approach by utilizing discussion groups, educational games, and the use of visual materials that are adjusted to the conditions of the students. KKL students also try to adapt the material according to the level of understanding and interests of the students, so that the learning process becomes more interesting and effective. The results of this activity show that the mentoring that was carried out succeeded in improving students' understanding, especially in understanding the importance of the values ​​of friendship contained in the History of Red and White and basic skills in Scouting. However, several obstacles, such as differences in student ability levels and limited supporting facilities, became obstacles that affected the smoothness of learning. The conclusion that can be drawn is that the mentoring material carried out by KKL students is effective in improving students' understanding, although there needs to be an increase in interaction with students and the use of more interesting media. Recommendations for the next mentoring activity are increasing the involvement of parents and teachers and the use of more modern learning aids to support a more comprehensive and sustainable learning process